Editorial bullying: an exploration of acts impacting publication ethics and related environment - Javed, Fawad; Michelogiannakis, Dimitrios; Rossouw, P. Emile (Frontiers in Research Metrics and Analytics, 2024)
Bullying and misconduct in the realm of scientific and scholarly publishing have the potential to jeopardize the transparency and integrity of academic discourse. While misconduct issues among authors have been extensively discussed, the role of editors in perpetuating or mitigating such problems has garnered less attention. Scientific publishing serves as the gateway for disseminating innovative research findings globally, and the role of editors, especially Editor/s-in-chief, is pivotal in safeguarding the rigor and credibility of published research. Editor bullying and misconduct involve behaviors that undermine the scientific process, compromise research integrity, and harm the careers and wellbeing of individuals. These actions may manifest as biased decision-making, suppression of dissenting voices, or the exploitation of power dynamics in the peer review process. To address these issues, preventive and therapeutic approaches are suggested, including enhancing awareness, recognizing and mitigating exacerbating factors, and upholding professionalism. Moreover, the importance of a conflict-of-interest declaration for editors is highlighted to ensure transparency and integrity in the editorial process. The present mini-review aims to shed light on editor bullying, illuminating its gravity and the urgency to address these issues within the academic publishing domain/s. This review underscores the more subtle, yet equally significant, issue of professional misconduct in the editorial realm of scientific journals.